2019
DOI: 10.1097/md.0000000000014955
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use and prostate cancer risk

Abstract: Background: The relationship between metformin use and the risk of prostate cancer is still inconclusive. Therefore, we performed a systematic review and meta-analysis of all eligible cohort studies to evaluate a potential association of metformin use with prostate cancer risk. Methods: A comprehensive literature search was performed in PubMed and Web of Science databases through July 2018. A DerSimonian and Laird random-effects model was applied to calculate the pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Such differences could be driven by differences in biases stemming from study design, such as differing levels of selection bias induced by inevitably only selected survivors of the exposure and competing risk. As such, it remains inconclusive whether the observed inverse relation between metformin and various cancers is a reflection of immortal time bias, notwithstanding the observations concerning metformin and prostate cancer are unclear 13. Results from randomized controlled trials and Mendelian randomization studies using genetic risk scores for AMPK in large well-designed biobanks would provide a more definitive answer to this important clinical question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences could be driven by differences in biases stemming from study design, such as differing levels of selection bias induced by inevitably only selected survivors of the exposure and competing risk. As such, it remains inconclusive whether the observed inverse relation between metformin and various cancers is a reflection of immortal time bias, notwithstanding the observations concerning metformin and prostate cancer are unclear 13. Results from randomized controlled trials and Mendelian randomization studies using genetic risk scores for AMPK in large well-designed biobanks would provide a more definitive answer to this important clinical question.…”
Section: Discussionmentioning
confidence: 99%
“…Others argued the approach to correct for immortal time bias remains controversial and requires additional validations 10. Potentially stronger study designs, such as the marginal structural models applied to electronic health records with inverse probability weighting,11 and Mendelian randomization using biomarkers of metformin12 did not provide strong evidence for a causal role of metformin in breast cancer, with similar findings for prostate cancer in a recent meta-analysis 13. Given the relation between antidiabetes medications and breast cancer risk appears to vary across classes of medication with different modes of actions (eg, metformin vs sulfonylurea),14 this may imply glycemic traits per se are not the main factors accounting for any reduction in cancer risk among metformin users.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen cohort or nested case-control studies were included with a total of 52,328 cases. In a random-effect pooled analysis, metformin use was not significantly associated with the risk of prostate cancer (RR 0.97, 95% CI 0.80-1.16, p = 0.711) [81].…”
Section: Metformin and Cancermentioning
confidence: 90%
“…After multivariable adjustment, the risk for the development of cancer among metformin users was not significantly different from that among controls (HR = 0.96; 95% confidence interval, 0.89-1.03; p = 0.250), suggesting a lack of association between metformin therapy and the risk of cancer among patients with diabetes [80]. Feng et al, conducted a meta-analysis of cohort studies to evaluate a potential association of metformin use with prostate cancer risk [81]. Eighteen cohort or nested case-control studies were included with a total of 52,328 cases.…”
Section: Metformin and Cancermentioning
confidence: 99%
“…A recent meta-analysis found no association between metformin use and prostate cancer risk (Relative risk was 0.97, 95% CI 0.80 to 1.16) but had significant heterogeneity between studies. 29 Similarly, another systematic review included a comprehensive bias evaluation and concluded that the studies least likely to be affected by bias did not support a causal effect of metformin on cancer risk. 30 A recent Taiwanese study found that treatment…”
Section: Comparison With the Exsting Literaturementioning
confidence: 99%